2016
DOI: 10.1371/journal.pone.0150928
|View full text |Cite
|
Sign up to set email alerts
|

Implied Spatial Meaning and Visuospatial Bias: Conceptual Processing Influences Processing of Visual Targets and Distractors

Abstract: Concepts with implicit spatial meaning (e.g., "hat", "boots") can bias visual attention in space. This result is typically found in experiments with a single visual target per trial, which can appear at one of two locations (e.g., above vs. below). Furthermore, the interaction is typically found in the form of speeded responses to targets appearing at the compatible location (e.g., faster responses to a target above fixation, after reading "hat"). It has been argued that these concept-space interactions could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Several subsequent studies observed facilitation instead of interference for targets in compatible location using very similar paradigms (Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012;Gozli, Chasteen, & Pratt, 2013;Gozli, Pratt, Martin, & Chasteen, 2016;Zhang et al, 2013). In a series of experiments, Gozli et al (2013) singled out the factors driving the direction of the effect and concluded that interference is likely to be observed at short stimulus onset asynchronies (SOAs) between cue words and targets (Ͻ400 ms) and when discrimination (as opposed to detection) tasks are used, whereas facilitation is typically obtained at longer SOAs or when detection tasks are used.…”
mentioning
confidence: 96%
“…Several subsequent studies observed facilitation instead of interference for targets in compatible location using very similar paradigms (Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012;Gozli, Chasteen, & Pratt, 2013;Gozli, Pratt, Martin, & Chasteen, 2016;Zhang et al, 2013). In a series of experiments, Gozli et al (2013) singled out the factors driving the direction of the effect and concluded that interference is likely to be observed at short stimulus onset asynchronies (SOAs) between cue words and targets (Ͻ400 ms) and when discrimination (as opposed to detection) tasks are used, whereas facilitation is typically obtained at longer SOAs or when detection tasks are used.…”
mentioning
confidence: 96%
“…Words with spatial associations can also guide visual attention to an associated location (i.e., a conceptual cueing effect ). For instance, words such as bird or hero can orient attention upwards, whereas words such as root or liar can orient attention downwards (Amer et al, 2018; Dudschig et al, 2013; Estes et al, 2015; Gozli et al, 2016). Such attentional bias has been found to interfere with visual perception at an associated location and thus, counterintuitively, hinders identification of visual targets.…”
mentioning
confidence: 99%